Menginterpretasikan Ulang Tanggung Jawab Sosial Perusahaan sebagai Strategi Keberlanjutan: Tinjauan Konseptual dari Perspektif RISAL di Indonesia - Risal Risal; Marwah Yusuf; Dahniyar Daud (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2026)
Corporate Social Responsibility (CSR) in Indonesia has shifted from being merely a legal obligation to a strategic instrument of sustainability. Regulations such as Law No. 40 of 2007 and Government Regulation No. 47 of 2012 mandate CSR implementation, yet practices in the field often remain symbolic. This article elaborates on the meaning of CSR from the “RISAL” perspective (Relevance of Environmental Accounting Strategy Implementation), emphasizing the integration of CSR with environmental accounting. The research method used is literature review with descriptive qualitative analysis. The findings highlight four key dimensions: (1) anxiety due to CSR being trapped in administrative compliance, (2) the need to search for clarity of meaning so CSR becomes an instrument of sustainability, (3) CSR as a compass guiding companies toward the horizon of the triple bottom line, and (4) small footprints of CSR programs that can create big waves in social legitimacy and business sustainability. This article asserts that CSR should not stop at the normative domain but must be lived as a meaningful sustainability strategy.